Draft Annual Plan 1970-71 Government of Himachal Pradesh - Planning Commission (Planning Commission, 1970)
Shimla, the biggest town and the capital of Himachal Pradesh, apart from being a big tourist resort, is a centre of commercial importance in the context of surrounding area which is backward in terms of entrepreneurial leadership, Its merger with Himachal Pradesh was rather very essential the tea gardens of Kangra, particularly of Palampur, and. orchards of Kulu are likely to prove valuable assets to the Pradesh. However, despite the inclusion of these new areas, the fundamental character of Himachal Pradesh even now remains essentially a rural based hill economy with few industrial units of significance.
Government of Himachal Pradesh, Planning Department